Electrocatalytic activity of symmetric and asymmetric Co(II) and Mn(III) porphyrins in the presence of graphene quantum dots towards the oxidation of hydrazine - Jokazi, Mbulelo (Rhodes University, Faculty of Science, Department of Chemistry)
The influence of metal porphyrins in electro-oxidation of hydrazine is explored. A series of symmetric and asymmetric porphyrins alone and in the presence of graphene quantum dots (GQDs) are employed in this work. Tetra 4-aminophenyl porphyrin, manganese tetra 4-aminophenyl porphyrin, manganese tetra 4-aminophenyl porphyrin--GQDs, and manganese tetra 4-aminophenyl porphyrin@GQDs are the symmetric porphyrins. The asymmetric porphyrin and composites are 5, 10, 15-tris(aminophenyl)-20-(4-carboxyphenyl) porphyrins, manganese 5, 10, 15-tris(aminophenyl)-20-(4-carboxyphenyl) porphyrins, cobalt 5, 10, 15-tris(aminophenyl)-20-(4-carboxyphenyl) porphyrins, manganese 5, 10, 15-tris(aminophenyl)-20-(4-carboxyphenyl) porphyrins--GQDs, and cobalt 5, 10, 15-tris(aminophenyl)-20-(4-carboxyphenyl) porphyrins--GQDs. These complexes were synthesized and characterized accordingly and applied for electrocatalysis. The electrocatalytic experiments were carried out using glassy carbon electrode and the modification was through drop-dry method. The porphyrin and GQDs synthesized were characterized using UV-Vis spectroscopy, Mass spectrometry, X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy and energy dispersive x-ray spectroscopy. The modified electrodes were characterized using cyclic voltammetry and electrochemical Impedance spectroscopy. The introduction of metal ion in the center of the porphyrin improved electrocatalysis. The presence of push-pull substituents in the porphyrin lowered the oxidation potential and improved the catalysis. The presence of GQDs improved catalysis in both symmetric and asymmetric porphyrin compared to individual components. Cobalt porphyrins showed better activity than manganese porphyrin.
Keywords: Electrocatalysis; Hydrazine; Quantum dots; Graphene; Porphyrins